Post-acute phase and sequelae management of epidermal necrolysis: an international, multidisciplinary DELPHI-based consensus - Ingen-Housz-Oro, S; Schmidt, V; Ameri, M M; Abe, R; Brassard, A; Mostaghimi, A; Paller, A S; Romano, A; Didona, B; Kaffenberger, B H; Ben Said, B; Thong, B Y H; et al. (Orphanet journal of rare diseases, 2023)
BACKGROUND: Long-term sequelae are frequent and often disabling after epidermal necrolysis (Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN)). However, consensus on the modalities of management of these sequelae is lacking. OBJECTIVES: We conducted an international multicentric DELPHI exercise to establish a multidisciplinary expert consensus to standardize recommendations regarding management of SJS/TEN sequelae. METHODS: Participants were sent a survey via the online tool "Survey Monkey" consisting of 54 statements organized into 8 topics: general recommendations, professionals involved, skin, oral mucosa and teeth, eyes, genital area, mental health, and allergy workup. Participants evaluated the level of appropriateness of each statement on a scale of 1 (extremely inappropriate) to 9 (extremely appropriate). Results were analyzed according to the RAND/UCLA Appropriateness Method. RESULTS: Fifty-two healthcare professionals participated. After the first round, a consensus was obtained for 100% of 54 initially proposed statements (disagreement index < 1). Among them, 50 statements were agreed upon as 'appropriate'; four statements were considered 'uncertain', and ultimately finally discarded. CONCLUSIONS: Our DELPHI-based expert consensus should help guide physicians in conducting a prolonged multidisciplinary follow-up of sequelae in SJS-TEN.
Keywords: Consensus; lidé; Stevensův-Johnsonův syndrom; konsensus; progrese nemoci; Skin; kůže; Disease Progression; Stevens-Johnson Syndrome; Humans